Utilization of Scrum Models in Photography Services and Online Videography - Vionika Angelia Fendrika; David David; Gat Gat; Sandy Kosasi; Tony Wijaya (Universitas Raharja, 2022)
The difficulties faced by the user in selecting photography and videography services are now very limited to access the transmission of his works, and also because a photography and videography have not been computerized to make information and data management scarce. The purpose of the study is to develop a software by pinching agile ux, asa measure of user satisfaction or need to online photography and videography services. The method is the scrum that serves to manage a project more efficiently, and it makes teamwork more effective and focused. The results of this study were developing a software that functioned asa function, from providers and users as well as photography and videography services, so they became more efficient and the published works became more optimized. Testing results using black box testing that test for functionality and required specifications. Applications made to help sell products and promote shops in these materials, so that all are more organized and more effective in the system are washed down. The application has not been entirely feasible, as development in the system is still required.